2021
DOI: 10.1002/1878-0261.12900
|View full text |Cite
|
Sign up to set email alerts
|

Combined RNA/tissue profiling identifies novel Cancer/testis genes

Abstract: Cancer/Testis (CT) genes are induced in germ cells, repressed in somatic cells, and derepressed in somatic tumors, where these genes can contribute to cancer progression. CT gene identification requires data obtained using standardized protocols and technologies. This is a challenge because data for germ cells, gonads, normal somatic tissues, and a wide range of cancer samples stem from multiple sources and were generated over substantial periods of time. We carried out a GeneChip-based RNA profiling analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 85 publications
(137 reference statements)
0
7
0
Order By: Relevance
“…Observations of the testes of PDCL2 -knockout mice revealed the loss of sperm acrosomal cap formation and malformed nuclei. It has also been reported that the PDCL2 protein is associated with the decreased survival of kidney cancer patients ( 31 ).…”
Section: Discussionmentioning
confidence: 94%
“…Observations of the testes of PDCL2 -knockout mice revealed the loss of sperm acrosomal cap formation and malformed nuclei. It has also been reported that the PDCL2 protein is associated with the decreased survival of kidney cancer patients ( 31 ).…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, SPESP1 knockdown induced cell senescence and accelerated skin ageing. While previous studies have linked SPESP1 to the growth and development of tumour diseases, 20 , 40 , 41 , 42 there remains a limited understanding of the functional roles and underlying mechanisms of SPESP1.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular biology and genomic approaches have led to the discovery of several hundred cancer testis genes, most of which are identified using gene expression on the mRNA level (mRNA expression described further in the text). However, the gene expression on the protein level (protein expression described further in the text) in the testis is still unclear, and the human protein atlas (HPA) has been used as a reference to determine the testicular proteome [25]. The HPA is a free-to-use and open-access platform with the aim of mapping all the human proteins in the body.…”
Section: Introductionmentioning
confidence: 99%